Gut microbiota, mood and disorders of gut-brain axis - S. Pletikosić Tončić; G. Hauser; M. Tkalčić (Microbiota in Health and Disease)
The main objective of this review is to summarize recent studies on the role of microbiota and microbial-targeted therapeutics in symptom relief and mood regulation of IBS patients. A PubMed search was performed to identify publications on the role of microbiota in disorders of the gut-brain axis published between March 2023 and March 2024. Six studies were included in the review: four on the effects of probiotic supplementation on GI IBS symptoms, mood, and microbiota, and two on the effects of specific diets on GI IBS symptoms, mood, and microbiota. In the first group of studies, probiotics containing the Bifidobacterium genus were applied. All studies reported a significant reduction of overall IBS symptoms, and most studies additionally reported a significant decrease in anxiety and/or depression in the intervention group compared to the placebo group. Some changes in bacterial abundance were reported. In the second group of studies, the Mediterranean diet and the low FODMAP diet both had a significant impact on GI symptom reduction, while the Mediterranean diet also improved depressive symptoms. Only the low FODMAP diet had a significant effect on microbiota composition. Probiotics and dietary interventions (Mediterranean and low FODMAP diet) could be useful for IBS symptom management. Additionally, these interventions may be beneficial for improving depression and anxiety symptoms in IBS patients.